Pedagogia virtuosa: os mo(vi)mentos da formação docente universitária - Santos, Fabiana Cabrera Silva (2022)
Teacher formation at university level has advanced significantly in education research. Such a horizon is open to new traces, among those which shed light on indispensable knowledge for pedagogical practice (Pimenta, 2012). In this sense, the research aims at interpreting teacher narratives in order to understand how their pedagogical knowledge has expanded, as well as their teacher professional identity. As for the theoretical-methodological frame, inspired by Paul Ricoeur’s text hermeneutics – through its Mimesis I, II, II – five narratives written by professors were unfolded. In Mimesis I – life before text – their experience is central, both in the text and in their teaching practice, in response to marketing education demands, expressed in Mimesis II. In Mimesis III, the text focuses on action, which brings about the so-called virtuous pedagogy based on oneself as another – an innovative path to develop teacher professional identity.(AU)